Preparation method of cement concrete doped with small amount of activated muck in high-alkali environment and prefabricated formwork column
By activating the slag in a high alkali environment and mixing it with cement, the problems of high cost, insufficient strength and environmental protection in the existing concrete preparation process are solved, and efficient and environmentally friendly concrete preparation is achieved, which improves the benefits of building industrialization development.
Patent Information
- Application Number
- CN202411696027.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-04-08
AI Technical Summary
There are high production costs, insufficient strength, poor construction performance and environmental protection problems in the preparation process of existing concrete, which is difficult to meet the needs of different construction projects.
The preparation method of adding a small amount of activated slag to cement concrete in a high alkali environment is adopted. By crushing and calcining the slag, and mixing it with cement under the action of an alkali activation agent, a green and low-carbon cementitious material is formed, reducing the amount of cement and improving the performance of concrete.
It reduces the production cost of concrete, improves the strength, seepage resistance, frost resistance and chemical corrosion resistance of concrete, extends the service life of the structure, reduces environmental pollution, and promotes the development of building industrialization.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and particularly relates to a preparation method of cement concrete mixed with a small amount of activated slag in a high-alkali environment and a prefabricated formwork column. Background Art
[0003] It is necessary to develop a type of concrete that can produce low cost, high strength, good working performance, and is green and environmentally friendly, so as to meet the use requirements of different construction projects. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings involved in the above concrete preparation process and provide a method for preparing cement concrete by adding a small amount of activated slag to cement concrete in a high-alkali environment.
[0005] The present invention adopts the following technical solutions: The method for preparing cement concrete by adding a small amount of activated slag in a high alkaline environment comprises the following steps: S1. Use a crusher to crush large pieces of construction slag, and after drying, use a grading crusher to grind them into slag powder; S2, calcining the slag powder in step S1 to form activated slag, and mixing the activated slag with cement and part of the admixture to form a mixture; S3, mixing sodium hydroxide, water glass and water to form an alkaline activator; S4, premixing the mixture of step S2 and the alkali liquor activator of step S3 to form a geopolymer slurry, adding the remaining admixture, sand and gravel and stirring to form concrete.
[0006] Specifically, the construction waste that originally needed to be transported to landfill can be effectively utilized, reducing the cost of waste disposal, improving the comprehensive utilization rate of resources, and complying with the concept of sustainable development. By partially replacing cement with activated waste, the dependence on cement is reduced without significantly affecting the performance of concrete, thus helping to reduce the production cost of concrete and saving material costs.
[0007] Specifically, in a high-alkali environment, the synergistic effect of activated slag and cement and other materials can optimize the microstructure of concrete and make it more compact. The formation of geopolymer slurry helps to fill the pores inside the concrete and reduce the intrusion path of harmful media, thereby enhancing the durability indicators of concrete such as impermeability, frost resistance and chemical corrosion resistance, extending the service life of concrete structures, and reducing the cost of later maintenance and reconstruction. Reasonable preparation technology and material matching can improve the workability of concrete, making it smoother during mixing, transportation, pouring and vibration, and less prone to problems such as segregation and bleeding, which is conducive to ensuring the quality of concrete construction and improving construction efficiency. Since the amount of cement used is reduced, the large amount of CO2 emissions generated by the calcination of limestone in the cement production process is indirectly reduced, which helps to alleviate the pressure of the construction industry on the environment.
[0008] Furthermore, the construction slag in step S1 is crushed to a particle size of less than 5 mm, and the slag powder is ground to a particle size of less than 1.5 mm; the crushed stone is made of granite crushed stone and slag crushed stone, and the granite crushed stone and slag crushed stone are mixed in a mass ratio of 1:1, and the crushed stone particle size is between 4-7 mm; the sand is graded sand and gravel with a particle size of less than 2.5 mm.
[0009] Specifically, the construction slag is crushed into a particle size of less than 5mm, and further ground into powder within 1.5mm. Such particle size refinement can increase the specific surface area of the slag, so that it can react more fully in the subsequent calcination and activation process, which is conducive to giving full play to the potential activity of the slag, better participating in the reaction system such as the gelling of concrete, and enhancing its effect on the performance of concrete. Smaller slag particle size helps it to be evenly dispersed in the concrete, avoiding local accumulation or weak areas caused by excessively large particles, thereby making the internal structure of the concrete more uniform and dense, improving the key performance indicators of concrete such as strength and impermeability from a microscopic level, and ensuring the stability of the overall quality of concrete.
[0010] Specifically, granite crushed stone has high strength and hardness, which can provide a solid support for concrete; and the slag crushed stone has good adaptability to the system after processing. The two work together to optimize the particle grading inside the concrete, making the gaps between the coarse aggregates smaller, thereby enhancing the bearing capacity of the concrete and improving mechanical properties such as compressive strength. Such a ratio can make the concrete achieve a good balance in terms of strength, toughness and durability. The appropriate crushed stone particle size range helps the concrete to mix better with other materials during the mixing process, avoiding uneven mixing due to excessive particle size. At the same time, it can also ensure that the concrete has good fluidity during pouring, and is not easy to block the gap between the formwork and the steel bars, ensuring the smooth progress of construction and improving construction efficiency.
[0011] Specifically, graded sand and gravel with a particle size of less than 2.5 mm is used. Its good grading can fill the gaps between the crushed stones, further optimize the particle stacking state of the concrete, and together with materials such as crushed stones, activated slag and cement, build a denser microstructure, improve the density of the concrete, and reduce the porosity, thereby enhancing the concrete's durability such as impermeability and frost resistance, and help improve the workability of the concrete, making it easier to shape and form during construction operations.
[0012] Furthermore, the calcination method of activated slag comprises the following steps: M1. The ground slag powder is placed in a muffle furnace and heated from room temperature to 750°C at a rate of 15°C per minute, and maintained at 750°C for 2.5 hours; Specifically, such a gradual and stable heating rate helps to evenly heat the components in the slag powder, avoiding local overheating caused by too rapid heating, so that the various mineral components and compounds inside the slag can gradually undergo physical and chemical changes under a suitable temperature gradient. The orderly adjustment of the mineral lattice structure, the gradual breaking and reorganization of chemical bonds, etc. are conducive to fully activating the potential active substances in the slag, making it have the potential to replace part of the cement as a cementitious material.
[0013] Specifically, at a temperature of 750°C, some clay minerals, aluminosilicates and other components in the slag can undergo reactions such as dehydroxylation, releasing active silicon and aluminum ions, which can participate in polymerization reactions in the subsequent reaction process of geopolymer slurry formation, generating gel substances that help improve the strength and durability of concrete, thereby better improving the performance of concrete. After reaching 750°C, the high temperature is maintained for 2.5 hours, which is enough time to make the various activation reactions inside the slag powder more thorough, and more potential active components are effectively stimulated, further improving the activity of the slag. Moreover, the constant temperature stage allows the active substances that have been generated to fully interact and diffuse with each other and with the components in the surrounding environment, making the chemical composition and microstructure of the entire slag powder more uniform and stable, laying a good foundation for the subsequent synergistic effect with cement, alkali activators, etc. to form high-quality geopolymer slurry and the final concrete.
[0014] M2. After heating is completed, the temperature in the muffle furnace chamber is naturally cooled to room temperature to form calcined activated slag.
[0015] Specifically, when the temperature in the muffle furnace cavity cools naturally to room temperature, the natural cooling process is relatively slow and steady, which avoids structural damage to the activated slag caused by sudden cooling. If a rapid cooling method is used, the already formed active structure will crack and break due to factors such as thermal stress, thereby affecting its subsequent reaction activity in concrete and the effect of improving concrete performance. Natural cooling can keep the activated slag in a relatively complete and stable microstructure, ensuring that it can continue to play its due role in subsequent processes such as mixing and stirring with other materials, which helps to ensure the quality consistency and performance reliability of the prepared concrete.
[0016] Furthermore, calculated by mass ratio, the ratio of 0.8-1.5% sodium hydroxide, water glass and water is 5-10:35-45:45-55.
[0017] Specifically, an appropriate amount of sodium hydroxide can provide a sufficient alkaline environment, promote water glass to better exert its excitation activity, accelerate the depolymerization reaction of silicate and other components in potential cementing materials such as activated soil and slag, and release more active silicon and aluminum ions, thereby creating favorable conditions for the subsequent generation of geopolymer gel and the construction of a three-dimensional network structure of concrete, which helps to enhance the strength and overall performance of concrete. If the amount of sodium hydroxide is too much, the alkalinity of the system will be too high. On the one hand, the setting time of concrete will be too fast, which is not conducive to construction operations. For example, it will set too early during mixing, transportation, and pouring, affecting construction efficiency and molding quality; on the other hand, too high alkalinity will have a strong corrosive effect on metal materials such as steel bars in concrete, reducing the durability of concrete structures, while a reasonable ratio can avoid these problems and ensure the balance and stability of concrete performance.
[0018] Specifically, sodium silicate and other ingredients in water glass can react with active ingredients in materials such as activated slag in an alkaline environment created by sodium hydroxide, and form inorganic polymer gels composed of elements such as Si and O through chemical processes such as polycondensation, filling the internal pores of concrete, enhancing the density of concrete, and improving its durability indicators such as impermeability and frost resistance. It also has a positive role in promoting the early strength development of concrete, so that concrete can obtain a certain bearing capacity in a relatively short period of time, which is conducive to speeding up the construction progress. This ratio range is compatible with the ratio of sodium hydroxide and water, and can work synergistically. The appropriate proportion of water glass ensures that there are enough silicon sources in the entire alkali activator system to participate in the polymerization reaction, and cooperates with sodium hydroxide to achieve efficient excitation of activated slag, etc. At the same time, it will not affect the overall excitation effect of the alkali activator and its compatibility with other raw materials in the concrete preparation process due to excessively high or low proportions, ensuring the good performance of all aspects of concrete performance.
[0019] Specifically, the proportion of water in the alkali activator is 45-55%, and water plays many important roles in the system. First, as a good solvent and reaction medium, it can fully dissolve and disperse sodium hydroxide and water glass, ensure that the various components of the alkali activator are evenly mixed, so as to ensure that the activating effect can be evenly exerted when in contact with the mixture, and avoid uneven local reactions. Secondly, an appropriate amount of water can adjust the fluidity of the alkali activator and subsequent concrete, making it easier to mix evenly during operations such as stirring and premixing, facilitating construction and molding, and ensuring good workability of concrete. It plays an indispensable role in ensuring the construction quality and appearance smoothness of concrete. The appropriate water ratio helps to maintain the stability of the entire alkali activator system, avoids the system being too thin due to excessive water, affecting the effective concentration and activating effect of the alkali activator, and prevents the alkali activator from being too thick due to too little water, making it difficult to fully mix with other materials and causing problems such as premature crystallization, thereby ensuring the smooth progress of the concrete preparation process and the reliable quality of the final product.
[0020] Furthermore, the activated slag and cement are mixed in a mass ratio of 1:4 to form a mixture.
[0021] Specifically, cement itself has high strength, which can provide a stable bonding effect for concrete and a good foundation for mechanical properties such as compression and flexural strength. After a series of treatments, activated slag also has a certain activity and can participate in the cementation reaction. Although its strength contribution alone is relatively limited, it is mixed with cement in a mass ratio of 1:4. The two complement each other, which not only ensures that the concrete as a whole has sufficient strength to meet the bearing requirements of the building structure, but also uses the activity of activated slag to further optimize the microstructure inside the concrete, making the strength development more reasonable and uniform, and improving the overall stability of the concrete structure.
[0022] Specifically, cement concrete has room for improvement in durability, such as resistance to chemical erosion and impermeability. Some active ingredients contained in activated slag, after mixing with cement, can participate in the hydration and other reactions of concrete, generate more dense gel substances to fill the pores, enhance the density of concrete, and improve its durability indicators such as impermeability and resistance to chemical erosion. The two are combined in this proportion to synergistically improve the durability of concrete, extend the service life of concrete structures in harsh environments, and reduce the cost of later repairs and maintenance.
[0023] Specifically, activated slag is used to replace part of the cement at a mass ratio of 1:4, which reduces the amount of cement without significantly affecting the performance of concrete, thereby effectively reducing the cost of raw materials for concrete. Most of the construction slag originally needed to be transported out for landfill treatment, which not only occupied a large amount of land resources, but also caused certain environmental problems. After being activated, it is mixed with cement in a certain proportion to achieve the resource reuse of construction slag, improve the comprehensive utilization rate of resources, conform to the concept of sustainable development, and at the same time reduce dependence on natural resources, and promote the construction industry to develop in a more green and environmentally friendly direction. The particle characteristics of activated slag and its proportion in the mixture, synergistically with cement, can have a positive effect on the workability of concrete. An appropriate amount of activated slag can adjust the workability indicators of concrete such as consistency and fluidity, making it smoother during mixing, transportation and pouring, less prone to problems such as segregation and water seepage, facilitating construction operations, and ensuring construction quality and efficiency.
[0024] Furthermore, the weight ratio of the mixture, sand, crushed stone and alkali activator is 0.8-1.2:1.5-2.0:2.5-3.5:0.25-0.75, and the admixture includes at least three of carbon fiber, steel fiber, waste shell powder, rubber powder, glass fiber, retarder and water reducer.
[0025] Specifically, the proportion range of the mixture, sand, gravel, and alkali activator ensures that the cementitious material can fully wrap aggregates such as sand and gravel to form a stable cementitious system. A sufficient amount of mixture can ensure that the concrete has good bonding properties, so that the various components are closely combined together, provide a reliable strength foundation for the concrete, and meet the mechanical performance requirements of different building structures in terms of load-bearing and compression resistance. This ratio allows the active ingredients carried by the activated slag in the mixture and the hydration products of cement to be reasonably distributed throughout the concrete and fully exert their effects, synergistically generating more gel substances that help improve the density and durability of the concrete, and optimizing the internal microstructure of the concrete, such as filling pores and strengthening the interface transition zone between aggregates and cementitious materials, thereby improving the long-term performance of the concrete, such as impermeability and chemical corrosion resistance.
[0026] Specifically, the weight ratio of sand is between 1.5-2.0, which can effectively fill the gaps between gravel and further improve the particle gradation of concrete. Fine sand particles can make the entire concrete structure more compact, reduce internal porosity, improve strength, and also play an important role in regulating the workability of concrete. Appropriate sand content can allow concrete to maintain good fluidity and plasticity during mixing, transportation and pouring, avoiding the situation of being too dry or too thin and soft, facilitating construction operations, and ensuring construction quality and efficiency.
[0027] Specifically, the weight ratio of crushed stone is between 2.5-3.5, which can provide a stable skeleton support structure for concrete. As the main coarse aggregate, crushed stone with larger particle size bears most of the structural load. With its high hardness and strength, it enhances the overall compression and flexural resistance of concrete, ensuring the stability and safety of the building structure during use. Moreover, the reasonable crushed stone ratio cooperates with sand, mixed materials, etc. to form a continuous and stable skeleton system inside the concrete, optimize the force transmission path, and improve the bearing capacity and structural integrity of the concrete.
[0028] Specifically, crushed stone works together with other materials to help improve the durability of concrete, reduce the risk of concrete cracking caused by factors such as shrinkage and temperature changes, and also play a positive role in resisting external physical wear and impact, thereby extending the service life of concrete structures, reducing subsequent maintenance costs, and adapting to building use needs under different environmental conditions.
[0029] Specifically, the alkali activator can fully stimulate the activity of the activated slag in the mixture, promote it to better polymerize with cement and other cementitious materials, and accelerate the formation of geopolymer gel. The appropriate amount of alkali activator not only ensures the efficient activation of the activated slag, but also does not cause excessive alkalinity in the system, resulting in negative problems such as abnormal concrete setting time and corrosion of steel bars, ensuring that the concrete performance reaches a good balance in terms of strength, durability and construction performance. This ratio allows the alkali activator to accurately control the chemical reaction process in the entire concrete system, coordinate the interaction between various materials, enable the concrete to achieve the ideal strength development within the appropriate time, and help optimize the formation of the internal microstructure of the concrete, enhance the comprehensive performance of the concrete, and meet the requirements for the setting time, early strength and long-term performance of the concrete during the construction process.
[0030] Specifically, the steel fiber includes a corrugated steel fiber or a fine steel fiber with a diameter between 0.1 and 0.3 mm. The corrugated steel fiber can increase the contact area with the cement base material and improve the bonding force. The fine steel fiber plays a role in bridging cracks in concrete. When the concrete is subjected to tension, the steel fiber can bear part of the tension and prevent the expansion of the cracks.
[0031] Specifically, steel fibers can effectively improve the tensile strength of concrete when accounting for 1%-1.5% of the total mass of the net paste, water, and coarse and fine aggregates. In some bending members such as beams and slab structures, the addition of steel fibers can significantly enhance the ability of concrete to resist bending and tensile damage, allowing the structure to withstand greater loads without brittle fracture. When the concrete structure is subjected to shear force, steel fibers can resist shear deformation through the bonding force with the concrete matrix. This is very important for structural members such as columns and shear walls that are subjected to large horizontal shear forces. Adding an appropriate amount of steel fibers can significantly improve the shear resistance of concrete and enhance the stability of the structure under horizontal forces such as earthquakes and wind loads. The presence of steel fibers gives concrete better toughness and can absorb more impact energy. Steel fiber concrete reduces damage and spalling on the concrete surface by resisting impact, thereby extending the service life of the structure. Since steel fibers can limit the development of cracks, they can reduce the intrusion of harmful substances such as moisture and chloride ions, thereby reducing the risk of durability problems such as steel bar corrosion and freeze-thaw damage in concrete.
[0032] Specifically, in some harsh environmental conditions, such as marine environment, chemical corrosion environment, etc., steel fiber concrete can better maintain the integrity of the structure. Because it improves the mechanical properties of concrete, it also indirectly enhances the resistance of the structure to environmental erosion, so that the concrete structure can maintain good performance during long-term use. Steel fibers accounting for 1%-1.5% of the total mass of the net slurry, water, and coarse and fine aggregates can provide sufficient restraint. Because the steel fibers are tightly bonded to the concrete matrix, the relative displacement of the internal particles of the concrete is limited, thereby reducing the structural deformation and even cracking caused by shrinkage and creep. The right amount of steel fibers can be evenly distributed during the concrete mixing process, and will not cause a significant deterioration in the working performance of the concrete. Moreover, during the concrete pouring process, steel fibers can help maintain the shape stability of the concrete, prevent local collapse or excessive deformation of the concrete during the vibration process, and ensure the smooth progress of the concrete construction. In the long run, the addition of steel fibers will improve the mechanical properties and durability of the concrete, reduce the number of repairs and reinforcements of the structure during use, and thus reduce the cost of the entire life cycle. Using steel fiber in a proportion of 1%-1.5% of the total mass of the neat paste, water, and coarse and fine aggregates can give full play to its reinforcing effect without significantly increasing the amount of steel fiber, thereby achieving the goal of economical and rational use of resources, and making the concrete meet the performance requirements while reducing costs as much as possible.
[0033] Specifically, carbon fiber includes polyacrylonitrile-based carbon fiber or asphalt-based carbon fiber, and carbon fiber has excellent mechanical properties such as ultra-high strength and modulus. Carbon fiber evenly dispersed in concrete can effectively share the load borne by concrete like "tendons and bones", and significantly improve the mechanical performance indicators of concrete such as tensile strength, flexural strength and impact toughness. In the case where the structure is subjected to tension, bending or impact, carbon fiber can inhibit the generation and expansion of cracks, enhance the overall toughness of the concrete structure, and make the structure more durable, especially suitable for some construction projects with high requirements for earthquake resistance and impact resistance. The addition of carbon fiber can also improve the durability and stability of concrete. It can prevent the intrusion of external corrosive media such as chloride ions and sulfates to a certain extent, and delay the deterioration process of concrete. At the same time, due to its good chemical stability, it can also maintain its own performance stability under complex environmental conditions, thereby improving the long-term service capacity of the entire concrete structure, reducing the number of repairs and replacements, and reducing the cost of the entire life cycle.
[0034] Specifically, the waste shell powder includes oyster shells and scallop shells. Specifically, the collected shells are first soaked and cleaned with an alkaline solution. Soaking the shells in a sodium hydroxide solution can effectively remove dirt, algae and organic residues on the surface of the shells, improve the purity of the shells and the effect of subsequent treatment. The concentration of the alkaline solution is 1M / L, and the soaking time is 1-2 hours to avoid damage to the shell structure and ensure effective cleaning. Then the cleaned shells are broken into shell particles and dried. The broken shells are easy to grind and process. Drying is to remove moisture from the shells to prevent agglomeration during the grinding process or uneven thermal expansion in subsequent processing. The broken shell particles are dried to ensure that the moisture content in the shell particles is minimized. The shell particles are ground into shell powder by ball milling; ball milling can grind the shell particles into fine powder, increase the specific surface area of the shell powder, and improve its dispersibility and reactivity in the composite material. Calcine at a temperature of 800°C to 1000°C for 2 hours and set aside. High-temperature calcination can completely remove organic matter in the shells, such as proteins and carbohydrates, and at the same time convert the calcium carbonate in the shells into calcium oxide, thereby improving the chemical and thermal stability of the shell powder.
[0035] Specifically, the preparation method of shell powder effectively improves the purity, fineness and stability of shell powder through the steps of soaking and cleaning, crushing and drying, ball milling and calcining. The spare discarded shell powder particles can play a certain lubricating role in the mixing process of materials such as concrete, improve the fluidity of the material, and facilitate construction operations. It can be filled in the tiny gaps between cement particles and aggregates to make the internal structure of the material more compact, which helps to improve the compressive strength and impermeability of the material. In addition, the discarded shell powder comes from shell waste, and it is used as a reinforcing agent to realize the reuse of waste resources and reduce the pollution of shell garbage to the environment, which is in line with the concept of sustainable development and environmental protection. Shell powder contains ingredients such as calcium carbonate. In an alkaline environment, it may react with cement hydration products to generate some substances with gelling properties, further enhancing the overall strength of the material.
[0036] Specifically, the rubber powder used is 80 mesh tire rubber powder, which can reduce resource waste while having good elasticity and toughness. After being added to the material, when the material is impacted by external force, the rubber powder can absorb and disperse the impact energy through its own elastic deformation, effectively improving the material's impact resistance, making it less likely to crack, break, or be damaged by sudden impact. It can give the material a certain degree of flexibility, reduce the brittleness of the material, and make the material less likely to have brittle fracture when it is deformed under load, but have a certain degree of elastic deformation ability.
[0037] Specifically, glass fiber includes alkali-resistant glass fiber or short-cut glass fiber, which has high strength and modulus. After being added to the material, it can bear part of the load like "tendons and bones", significantly improving the tensile strength and flexural strength of the material. In concrete, glass fiber can effectively resist the expansion of cracks caused by tension, making the material less likely to be damaged when subjected to bending, stretching and other loads, and enhancing the overall bearing capacity of the structure. It can form a randomly distributed fiber reinforcement network inside the material. When the material has microcracks due to shrinkage, temperature changes or stress, the glass fiber can cross the cracks to prevent further expansion of the cracks, improve the material's crack resistance, and ensure the integrity and durability of the material structure.
[0038] Specifically, due to the inhibitory effect of glass fiber on crack expansion, the channels for harmful substances from the outside (such as moisture, chemically corrosive substances, etc.) to intrude into the material through cracks are reduced, thereby enhancing the material's resistance to environmental erosion and extending the material's service life. The presence of glass fiber can constrain the relative displacement of particles inside the material, help reduce shrinkage deformation, creep and other phenomena during the hardening process of the material, improve the dimensional stability of the material, and ensure that the structure will not affect its function due to excessive deformation during long-term use.
[0039] Specifically, the retarder includes one of calcium ethylenediaminetetramethylenephosphonate, sodium carboxymethylcellulose, and sodium gluconate, and the retarder can delay the coagulation and hardening process of the material. During the construction of some large-scale projects or in high-temperature environments, materials such as concrete may coagulate too quickly, resulting in difficulties in construction operations. After adding the retarder, the initial and final setting times of the material can be appropriately extended according to actual construction needs, so that construction personnel have more time to perform operations such as mixing, transportation, pouring, and vibration to ensure construction quality. The retarder slows down the hydration rate of cement, making the heat release smoother, reducing the possibility of cracks in the concrete due to temperature stress, and improving the integrity and durability of large-volume concrete structures.
[0040] Specifically, the water reducer includes calcium lignin sulfonate, a polycarboxylic acid water reducer with a main chain of methacrylic acid and methyl acrylate copolymer and a side chain of polyoxyethylene. The water reducer can reduce the water-binder ratio in the concrete material, and reduce the amount of water while maintaining the same fluidity. It can effectively avoid the adverse phenomena of material segregation, water seepage, etc., and ensure the uniformity and quality of construction.
[0041] Specifically, water reducers reduce the water-cement ratio, which reduces the porosity inside the material and makes the structure more compact. After cement and other cementitious materials are hydrated, more and denser hydration products can be formed, thereby improving the mechanical properties of the material such as compressive strength and flexural strength. By reducing the channels for external moisture and chemically corrosive substances to enter the material, the material's resistance to durability problems such as freeze-thaw cycles and chemical corrosion is enhanced, the service life of the material is extended, and its stability for long-term use under different environmental conditions is improved. On the basis of maintaining the working performance and strength requirements of the material, the use of water reducers can appropriately reduce the amount of cement used, which not only helps to reduce production costs, but also reduces the consumption of natural resources and the emission of pollutants such as carbon dioxide during cement production.
[0042] Further, calcium hydroxide comprises the following preparation steps: N1. Limestone particles are sent from the raw material bin to the preheater to exchange heat with the high-temperature exhaust gas from the calcining furnace to increase the temperature of the limestone; Specifically, in step N1, limestone particles are sent to a preheater for heat exchange with the high-temperature exhaust gas from the calcining furnace, making full use of the heat contained in the exhaust gas discharged from the calcining furnace. The limestone is heated in advance through heat exchange, and heat recovery and reuse are achieved, effectively reducing energy consumption in the entire production process. After the heat exchange, the temperature of the limestone increases, and the conditions required for the reaction can be reached more quickly when entering the subsequent process. This preheating treatment allows the decomposition reaction of the limestone in the rotary kiln to start more quickly and fully, reducing the additional heating time and energy input required to reach the decomposition reaction temperature in the rotary kiln, improving the overall production efficiency, and accelerating the preparation process of calcium hydroxide.
[0043] N2, the preheated limestone enters the rotary kiln and decomposes into calcium oxide at 800℃-1200℃; Specifically, in the temperature range of 800℃-1200℃, the calcium carbonate in the limestone can be stably and efficiently decomposed into calcium oxide and carbon dioxide, which not only ensures the sufficiency of the decomposition reaction and converts as much limestone as possible into the target product calcium oxide, but also avoids problems such as incomplete reaction, increased side reactions or increased equipment loss caused by too high or too low temperature, which helps to ensure the quality and output of calcium oxide products. As a commonly used and mature industrial production equipment, the rotary kiln has the characteristics of uniform heating of materials and continuous production. The limestone tumbles continuously in the rotary kiln, which can ensure that each particle is evenly exposed to the heat, making the decomposition reaction of the entire material more uniform and thorough, avoiding local overheating or insufficient reaction, thereby producing calcium oxide with stable quality and high purity, laying a solid foundation for the subsequent preparation of high-quality calcium hydroxide.
[0044] N3, calcium oxide reacts with water to obtain calcium hydroxide.
[0045] Specifically, the chemical reaction principle of calcium oxide reacting with water to obtain calcium hydroxide is relatively simple and direct. The reaction can be carried out smoothly under normal conditions, does not require complicated reaction conditions or special catalysts, etc., is simple and easy to operate, and is easy to achieve industrial large-scale production.
[0046] Further, the water glass comprises the following preparation steps: P1, quartz sand and soda ash are mixed evenly in a weight ratio of 1:1.35, and the mixed raw materials are put into a high-temperature reverberatory furnace and calcined at a high temperature of 1400°C-1500°C for one hour to generate molten sodium silicate; Specifically, quartz sand and soda ash are uniformly mixed in a weight ratio of 1:1.35, which can ensure that in the subsequent high-temperature calcination process, the silicon dioxide in the quartz sand and the sodium carbonate in the soda ash can fully and completely react chemically to generate the target product molten sodium silicate, avoiding problems such as incomplete reaction or excess raw material residue due to improper raw material ratio, thereby ensuring the purity and quality of the sodium silicate product and providing high-quality basic raw materials for the subsequent preparation of water glass.
[0047] Specifically, the high temperature of 1400℃-1500℃ can break the stable lattice structure of silicon dioxide in quartz sand and the chemical bonds of sodium carbonate in soda ash, causing the atoms and ions of the two to fully activate and recombine, and chemically react to form sodium silicate. Secondly, the one-hour calcination time ensures that the reaction has enough time to complete, so that the raw materials can be fully converted into molten sodium silicate, thereby increasing the yield of the product. Moreover, the high temperature environment of the high-temperature reverberatory furnace is relatively uniform and stable, which allows the entire raw material system to be heated evenly, avoiding local overheating or uneven reactions, and further ensuring the uniformity of the chemical composition and physical properties of the generated sodium silicate, which is conducive to subsequent processing and application.
[0048] P2. Add sodium silicate granules to the steam ball and add water to form a water glass solution. Adding sodium silicate granules to the steam ball and adding water to form a water glass solution is relatively simple and easy to operate. The steam ball provides a good reaction and mixing place. By adding water and stirring and mixing inside it, the sodium silicate granules can be quickly and evenly dissolved in water and efficiently converted into a water glass solution. This morphological transformation from solid granules to liquid solution facilitates the subsequent addition of water glass to the alkali activator in an appropriate proportion, so as to better participate in the alkali-activated reaction in the preparation process of activated slag alkali-activated concrete, and ensure that it can be evenly dispersed and play a role in the concrete system. The formed water glass solution has good fluidity and operability. Compared with solid sodium silicate, it is easier to mix with other ingredients (such as calcium hydroxide, etc.) in the alkali activator, and can better penetrate and diffuse when in contact with the mixture, so that the alkali-activated reaction is carried out more evenly in the entire concrete system.
[0049] Further, the sodium hydroxide comprises the following preparation steps: Q1. Dissolve the raw salt, remove impurities through filtration, sedimentation and ion exchange to obtain refined brine; Specifically, in step Q1, after the raw salt is dissolved, impurities are removed by filtering, sedimentation, ion exchange and other treatment methods in turn. This series of operations can effectively purify the raw salt solution. Filtration can screen out insoluble large particles of impurities, sedimentation can allow some suspended fine particles to settle down by gravity, and ion exchange treatment can specifically remove various harmful ion impurities in the solution, such as calcium ions, magnesium ions, etc. Through these comprehensive impurity removal measures, the purity of the obtained refined brine is greatly improved, which lays a solid foundation for the subsequent electrolytic preparation of high-quality sodium hydroxide, avoids the adverse effects of impurities on electrodes, electrolytic cells and other equipment during the subsequent electrolysis process, and also ensures the purity and quality of the final sodium hydroxide product.
[0050] Specifically, the refined brine after removing impurities can participate in the reaction more stably in the subsequent production links. Because the presence of impurities can cause problems such as electrode scaling and fluctuations in electrolysis efficiency, the purified refined brine can make the electrolysis process proceed stably as expected, reduce failures and abnormalities in the production process, improve the reliability and continuity of the entire production system, and facilitate the large-scale and efficient production of sodium hydroxide, ensuring production efficiency and output.
[0051] Q2. Pass the refined brine into an electrolytic cell and pass direct current for electrolysis to obtain sodium hydroxide.
[0052] Specifically, the refined brine is passed into an electrolytic cell and direct current is passed for electrolysis to produce sodium hydroxide. The electrolysis process is based on electrochemical principles. Under the action of direct current, components such as sodium chloride in the refined brine solution can undergo precise redox reactions to generate sodium hydroxide, hydrogen, chlorine and other products at the cathode and anode respectively. The reaction has high selectivity and conversion rate, and can produce sodium hydroxide products in a large and stable manner. The sodium hydroxide generated by electrolysis can be separated from the electrolytic cell more conveniently to meet the needs of industrial applications of different scales.
[0053] Furthermore, another object of the present invention is to provide a prefabricated formwork column, which is made of concrete obtained by adding a small amount of activated slag to cement concrete in a high-alkali environment as described above.
[0054] Specifically, because the activated slag in the concrete has undergone specific crushing, calcination and other treatments, and is mixed with cement in a suitable proportion, and under the action of an alkali activator, the various components synergistically form a good gelling system, and its internal microstructure is relatively dense. Using such concrete to make prefabricated formwork columns can give the formwork columns a higher compressive strength, which is sufficient to withstand the effects of various forces such as vertical loads in the building structure and ensure the stability of the entire structure. At the same time, the durability indicators of concrete such as impermeability, frost resistance and chemical corrosion resistance are enhanced. During long-term use, the prefabricated formwork columns are not prone to internal steel corrosion, concrete peeling and other degradation phenomena even if they are affected by external factors such as rain erosion, temperature changes and contact with chemical substances. This greatly extends the service life of the prefabricated formwork columns and even the entire building structure, and reduces the cost of later maintenance and replacement.
[0055] Specifically, when preparing the concrete, the particle size and proportion of the raw materials are carefully controlled, so that the concrete has good workability. During the casting and molding process of the prefabricated formwork column, the concrete can better fill every corner of the mold, avoiding quality defects such as honeycomb surface and voids, ensuring the appearance quality and dimensional accuracy of the prefabricated formwork column, and improving the qualified rate of the product. The use of engineering slag to partially replace cement after activation reduces the dependence on relatively high-priced cement and directly reduces the cost of raw materials. For the large-scale production of prefabricated formwork columns, this cost-saving effect is very significant, which helps to improve the competitiveness of the product in the market and obtain better economic benefits while meeting the structural performance requirements. Because the amount of cement is reduced, the large amount of carbon dioxide emissions generated by the calcination of limestone in the cement production process is indirectly reduced. The production process of the prefabricated formwork column becomes a process of turning waste into treasure and improving the environment, which is conducive to creating a good ecological environment.
[0056] Compared with the prior art, the present invention has the following advantages: 1. The present invention provides a method for preparing cement concrete by adding a small amount of activated slag in a high-alkali environment and a prefabricated formwork column. The engineering slag is crushed, dried, and ground, and then calcined and activated. Under the action of an alkaline activator, a green and low-carbon cementitious material is formed and added to cement concrete to reduce the amount of cement that is high in energy consumption and pollution.
[0057] 2. The present invention adopts concrete mixed with activated slag to make prefabricated formwork columns, which can give full play to its advantages of rapid hardening, early strength and high strength, and promote the development of building industrialization while reducing resource waste and environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 It is a schematic cross-sectional view of the prefabricated formwork column of the present invention.
[0059] Figure 2It is a schematic cross-sectional view of the prefabricated formwork column of the present invention.
[0060] Figure 3 It is a schematic diagram of PM curve analysis of the prefabricated formwork column of the present invention. DETAILED DESCRIPTION
[0061] In order to make those skilled in the art more clearly understand the technical solution of the present invention, the following examples are listed for illustration. Unless otherwise specified, the raw materials, reagents or devices used in the following embodiments can be obtained from conventional commercial channels or can be obtained by existing known methods.
[0062] The present invention will be further described below in conjunction with specific embodiments: The method for preparing cement concrete by adding a small amount of activated slag in a high alkaline environment comprises the following steps: S1. Use a crusher to crush large pieces of construction slag, and after drying, use a grading crusher to grind them into slag powder; S2, calcining the slag powder in step S1 to form activated slag, and mixing the activated slag with cement and part of the admixture to form a mixture; S3, mixing sodium hydroxide, water glass and water to form an alkaline activator; S4, premixing the mixture of step S2 and the alkali liquor activator of step S3 for 15 minutes to form a geopolymer slurry, and adding the remaining admixtures, sand and gravel to stir to form concrete.
[0063] Furthermore, the construction slag in step S1 is crushed to a particle size of less than 5 mm, and the slag powder is ground to a particle size of less than 1.5 mm; the crushed stone is made of granite crushed stone and slag crushed stone, and the granite crushed stone and slag crushed stone are mixed in a mass ratio of 1:1, and the crushed stone particle size is between 4-7 mm; the sand is graded sand and gravel with a particle size of less than 2.5 mm.
[0064] The calcination method of activated slag comprises the following steps: M1. The ground slag powder is placed in a muffle furnace and heated from room temperature to 750°C at a rate of 15°C per minute, and maintained at 750°C for 2.5 hours; M2. After heating is completed, the temperature in the muffle furnace chamber is naturally cooled to room temperature to form calcined activated slag.
[0065] Calculated by mass ratio, the ratio of 0.8-1.5% sodium hydroxide, water glass and water is 5-10:35-45:45-55.
[0066] The activated slag and cement are mixed in a mass ratio of 1:4 to form a mixture.
[0067] The weight ratio of the mixture, sand, crushed stone and alkali activator is 0.8-1.2:1.5-2.0:2.5-3.5:0.25-0.75, and the admixture includes at least three of carbon fiber, steel fiber, waste shell powder, rubber powder, glass fiber, retarder and water reducer. The carbon fiber accounts for 0.5%-0.8% of the total mass of the mixture, sand, gravel and alkali activator, the steel fiber accounts for 1%-1.5% of the total mass of the mixture, sand, gravel and alkali activator, the waste shell powder accounts for 0.5%-1.5% of the total mass of the mixture, sand, gravel and alkali activator, the rubber powder accounts for 1%-1.5% of the total mass of the mixture, sand, gravel and alkali activator, the glass fiber accounts for 0.5%-1.0% of the total mass of the mixture, sand, gravel and alkali activator, the retarder accounts for 0.1%-0.3% of the total mass of the mixture, sand, gravel and alkali activator, and the water reducer accounts for 0.3%-0.5% of the total mass of the mixture, sand, gravel and alkali activator.
[0068] The steel fibers include corrugated steel fibers or fine steel fibers with a diameter between 0.1 and 0.3 mm.
[0069] The carbon fibers include polyacrylonitrile-based carbon fibers or pitch-based carbon fibers with a diameter of 5-10 μm.
[0070] Waste shell powder includes oyster shells and scallop shells. The collected shells are first soaked and cleaned in 1M / L NaOH alkaline solution for 12 hours, and then the cleaned shells are broken into 200 mesh shell particles, dried, and ground into shell powder by ball milling. The powder is calcined at 800°C for 2 hours and set aside.
[0071] The rubber powder used is 80 mesh tire rubber powder processed by Shengfei Minerals.
[0072] The glass fibers include alkali-resistant glass fibers or chopped glass fibers having a diameter of 5-20 mm.
[0073] The retarder includes one of calcium ethylenediaminetetramethylenephosphonate, sodium carboxymethylcellulose and sodium gluconate.
[0074] The water reducing agent includes calcium lignin sulfonate, a polycarboxylic acid water reducing agent whose main chain is composed of a copolymer of methacrylic acid and methyl acrylate and whose side chain is polyoxyethylene.
[0075] Calcium hydroxide comprises the following preparation steps: N1. Limestone particles are sent from the raw material bin to the preheater to exchange heat with the high-temperature exhaust gas from the calcining furnace to increase the temperature of the limestone; N2, the preheated limestone enters the rotary kiln and decomposes into calcium oxide at 800℃-1200℃; N3, calcium oxide reacts with water to obtain calcium hydroxide.
[0076] Water glass comprises the following preparation steps: P1, quartz sand and soda ash are mixed evenly in a weight ratio of 1:1.35, and the mixed raw materials are put into a high-temperature reverberatory furnace and calcined at a high temperature of 1400°C-1500°C for one hour to generate molten sodium silicate; P2. Add sodium silicate granules into the steam ball and add water to form a water glass solution.
[0077] Sodium hydroxide comprises the following preparation steps: Q1. Dissolve the raw salt, remove impurities through filtration, sedimentation and ion exchange to obtain refined brine; Q2. Pass the refined brine into an electrolytic cell and pass direct current for electrolysis to obtain sodium hydroxide.
[0078] Example 1 The method for preparing cement concrete by adding a small amount of activated slag in a high alkaline environment comprises the following steps: S1. Use a crusher to crush large pieces of construction slag, and after drying, use a grading crusher to grind them into slag powder; S2, calcining the slag powder in step S1 to form activated slag, and mixing the activated slag with cement and a water reducing agent to form a mixture; S3, mixing sodium hydroxide, water glass and water to form an alkaline activator; S4, premixing the mixture of step S2 and the alkali liquor activator of step S3 for 15 minutes to form a geopolymer slurry, and adding the remaining admixtures, sand and gravel to stir to form concrete.
[0079] The construction slag in step S1 is crushed to a particle size of 3 mm, and the slag powder is ground to 1.0 mm; the crushed stone is made of granite crushed stone and slag crushed stone, which are mixed in a mass ratio of 1:1, and the crushed stone particle size is 4 mm; the sand is graded sand and gravel with a particle size of 2.0 mm.
[0080] The calcination method of activated slag comprises the following steps: M1. The ground slag powder is placed in a muffle furnace and heated from room temperature to 750°C at a rate of 15°C per minute, and maintained at 750°C for 2.5 hours; M2. After heating is completed, the temperature in the muffle furnace chamber is naturally cooled to room temperature to form calcined activated slag.
[0081] Calculated by mass, the ratio of 1.5% sodium hydroxide, water glass and water is 5:35:55.
[0082] The activated slag and cement are mixed in a mass ratio of 1:4 to form a mixture.
[0083] The weight ratio of the mixture, sand, crushed stone and alkali activator is 0.8:1.5:2.5:0.25. The admixtures include carbon fiber, steel fiber, waste shell powder, rubber powder, glass fiber and water reducer. The carbon fiber accounts for 0.8% of the total mass of the pure slurry, water and coarse and fine aggregates, the steel fiber accounts for 1.5% of the total mass of the pure slurry, water and coarse and fine aggregates, the waste shell powder accounts for 1.0% of the total mass of the pure slurry, water and coarse and fine aggregates, the rubber powder accounts for 1% of the total mass of the pure slurry, water and coarse and fine aggregates, the glass fiber accounts for 0.5% of the total mass of the pure slurry, water and coarse and fine aggregates, and the water reducer accounts for 0.3% of the total mass of the pure slurry, water and coarse and fine aggregates. The steel fiber is a fine steel fiber with a diameter of 0.1 mm.
[0084] The carbon fiber is polyacrylonitrile-based carbon fiber with a diameter of 5 μm.
[0085] The glass fiber is an alkali-resistant glass fiber with a diameter of 20 mm.
[0086] The water reducer is a kind of polycarboxylic acid water reducer with the main chain being a copolymer of methacrylic acid and methyl acrylate and the side chain being a polyoxyethylene.
[0087] Calcium hydroxide comprises the following preparation steps: N1. Limestone particles are sent from the raw material bin to the preheater to exchange heat with the high-temperature exhaust gas from the calcining furnace to increase the temperature of the limestone; N2, the preheated limestone enters the rotary kiln and decomposes into calcium oxide at 800℃; N3, calcium oxide reacts with water to obtain calcium hydroxide.
[0088] Water glass comprises the following preparation steps: P1, quartz sand and soda ash are mixed evenly in a weight ratio of 1:1.35, and the mixed raw materials are put into a high-temperature reverberatory furnace and calcined at a high temperature of 1400°C for one hour to generate molten sodium silicate; P2. Add sodium silicate granules into the steam ball and add water to form a water glass solution.
[0089] Sodium hydroxide comprises the following preparation steps: Q1. Dissolve the raw salt, remove impurities through filtration, sedimentation and ion exchange to obtain refined brine; Q2. Pass the refined brine into an electrolytic cell and pass direct current for electrolysis to obtain sodium hydroxide.
[0090] Example 2 The method for preparing cement concrete by adding a small amount of activated slag in a high alkaline environment comprises the following steps: S1. Use a crusher to crush large pieces of construction slag, and after drying, use a grading crusher to grind them into slag powder; S2, calcining the slag powder in step S1 to form activated slag, and mixing the activated slag with cement and a water reducing agent to form a mixture; S3, mixing sodium hydroxide, water glass and water to form an alkaline activator; S4, premixing the mixture of step S2 and the alkali liquor activator of step S3 for 15 minutes to form a geopolymer slurry, and adding the remaining admixtures, sand and gravel to stir to form concrete.
[0091] Furthermore, the construction slag in step S1 is crushed to a particle size of 4 mm, and the slag powder is ground to 0.5 mm; the crushed stone is made of granite crushed stone and slag crushed stone, and the granite crushed stone and slag crushed stone are mixed in a mass ratio of 1:1, and the crushed stone particle size is 7 mm; the sand uses graded sand and gravel with a particle size of 1.5 mm.
[0092] The calcination method of activated slag comprises the following steps: M1. The ground slag powder is placed in a muffle furnace and heated from room temperature to 750°C at a rate of 15°C per minute, and maintained at 750°C for 2.5 hours; M2. After heating is completed, the temperature in the muffle furnace chamber is naturally cooled to room temperature to form calcined activated slag.
[0093] Calculated by mass, the ratio of 0.8% sodium hydroxide, water glass and water is 10:45:45.
[0094] The activated slag and cement are mixed in a mass ratio of 1:4 to form a mixture.
[0095] The weight ratio of the mixture, sand, crushed stone and alkali activator is 1.2:2.0:3.5:0.75. The admixtures include carbon fiber, steel fiber, rubber powder, glass fiber and water reducer. The carbon fiber accounts for 0.8% of the total mass of the pure slurry, water and coarse and fine aggregates, the steel fiber accounts for 1.5% of the total mass of the pure slurry, water and coarse and fine aggregates, the rubber powder accounts for 1.5% of the total mass of the pure slurry, water and coarse and fine aggregates, the glass fiber accounts for 1.0% of the total mass of the pure slurry, water and coarse and fine aggregates, and the water reducer accounts for 0.5% of the total mass of the pure slurry, water and coarse and fine aggregates. The steel fiber is a wavy steel fiber with a diameter of 0.3mm.
[0096] The carbon fiber is asphalt-based carbon fiber with a diameter of 10 μm.
[0097] The glass fibers were chopped glass fibers with a diameter of 20 mm.
[0098] The water reducing agent is calcium lignin sulfonate.
[0099] Calcium hydroxide comprises the following preparation steps: N1. Limestone particles are sent from the raw material bin to the preheater to exchange heat with the high-temperature exhaust gas from the calcining furnace to increase the temperature of the limestone; N2, the preheated limestone enters the rotary kiln and decomposes into calcium oxide at 1200℃; N3, calcium oxide reacts with water to obtain calcium hydroxide.
[0100] Water glass comprises the following preparation steps: P1, quartz sand and soda ash are mixed evenly in a weight ratio of 1:1.35, and the mixed raw materials are put into a high-temperature reverberatory furnace and calcined at a high temperature of 1500°C for one hour to generate molten sodium silicate; P2. Add sodium silicate granules into the steam ball and add water to form a water glass solution.
[0101] Sodium hydroxide comprises the following preparation steps: Q1. Dissolve the raw salt, remove impurities through filtration, sedimentation and ion exchange to obtain refined brine; Q2. Pass the refined brine into an electrolytic cell and pass direct current for electrolysis to obtain sodium hydroxide.
[0102] Example 3 The method for preparing cement concrete by adding a small amount of activated slag in a high alkaline environment comprises the following steps: S1. Use a crusher to crush large pieces of construction slag, and after drying, use a grading crusher to grind them into slag powder; S2, calcining the slag powder in step S1 to form activated slag, and mixing the activated slag with cement and retarder to form a mixture; S3, mixing sodium hydroxide, water glass and water to form an alkaline activator; S4, premixing the mixture of step S2 and the alkali liquor activator of step S3 for 15 minutes to form a geopolymer slurry, and adding the remaining admixtures, sand and gravel to stir to form concrete.
[0103] Furthermore, the construction slag in step S1 is crushed to a particle size of 2 mm, and the slag powder is ground to within 0.5 mm; the crushed stone adopts granite crushed stone and slag crushed stone, and the granite crushed stone and slag crushed stone are mixed in a mass ratio of 1:1, and the crushed stone particle size is between 5 mm; the sand adopts graded sand and gravel with a particle size of 1.5 mm.
[0104] The calcination method of activated slag comprises the following steps: M1. The ground slag powder is placed in a muffle furnace and heated from room temperature to 750°C at a rate of 15°C per minute, and maintained at 750°C for 2.5 hours; M2. After heating is completed, the temperature in the muffle furnace chamber is naturally cooled to room temperature to form calcined activated slag.
[0105] Calculated by mass, the ratio of 0.8% sodium hydroxide, water glass and water is 10:35:55.
[0106] The activated slag and cement are mixed in a mass ratio of 1:4 to form a mixture.
[0107] The weight ratio of the mixture, sand, crushed stone and alkali activator is 0.8:2.0:3.5:0.75. The admixtures include steel fiber, waste shell powder and retarder. The steel fiber accounts for 1.5% of the total mass of the neat paste, water and coarse and fine aggregates, the waste shell powder accounts for 0.5% of the total mass of the neat paste, water and coarse and fine aggregates, and the retarder accounts for 0.3% of the total mass of the neat paste, water and coarse and fine aggregates.
[0108] The steel fiber is a fine steel fiber with a diameter of 0.3 mm.
[0109] The retarder is sodium carboxymethyl cellulose.
[0110] Calcium hydroxide comprises the following preparation steps: N1. Limestone particles are sent from the raw material bin to the preheater to exchange heat with the high-temperature exhaust gas from the calcining furnace to increase the temperature of the limestone; N2, the preheated limestone enters the rotary kiln and decomposes into calcium oxide at 1000℃; N3, calcium oxide reacts with water to obtain calcium hydroxide.
[0111] Water glass comprises the following preparation steps: P1, quartz sand and soda ash are mixed evenly in a weight ratio of 1:1.35, and the mixed raw materials are put into a high-temperature reverberatory furnace and calcined at a high temperature of 1500°C for one hour to generate molten sodium silicate; P2. Add sodium silicate granules into the steam ball and add water to form a water glass solution.
[0112] Sodium hydroxide comprises the following preparation steps: Q1. Dissolve the raw salt, remove impurities through filtration, sedimentation and ion exchange to obtain refined brine; Q2. Pass the refined brine into an electrolytic cell and pass direct current for electrolysis to obtain sodium hydroxide.
[0113] Example 4 The method for preparing cement concrete by adding a small amount of activated slag in a high alkaline environment comprises the following steps: S1. Use a crusher to crush large pieces of construction slag, and after drying, use a grading crusher to grind them into slag powder; S2, calcining the slag powder in step S1 to form activated slag, and mixing the activated slag with cement and a water reducing agent to form a mixture; S3, mixing sodium hydroxide, water glass and water to form an alkaline activator; S4, premixing the mixture of step S2 and the alkali liquor activator of step S3 for 15 minutes to form a geopolymer slurry, and adding the remaining admixtures, sand and gravel to stir to form concrete.
[0114] Furthermore, the construction slag in step S1 is crushed to a particle size of 3 mm, and the slag powder is ground into 1.25 mm; the crushed stone adopts granite crushed stone and slag crushed stone, and the granite crushed stone and slag crushed stone are mixed in a mass ratio of 1:1, and the crushed stone particle size is 4 mm; the sand adopts graded sand and gravel with a particle size of 2.0 mm.
[0115] The calcination method of activated slag comprises the following steps: M1. The ground slag powder is placed in a muffle furnace and heated from room temperature to 750°C at a rate of 15°C per minute, and maintained at 750°C for 2.5 hours; M2. After heating is completed, the temperature in the muffle furnace chamber is naturally cooled to room temperature to form calcined activated slag.
[0116] Calculated by mass, the ratio of 1.5% sodium hydroxide, water glass and water is 10:45:55.
[0117] The activated slag and cement are mixed in a mass ratio of 1:4 to form a mixture.
[0118] The weight ratio of the mixture, sand, crushed stone and alkali activator is 1.2:2.0:2.5:0.25, and the admixtures include carbon fiber, steel fiber, waste shell powder, rubber powder, glass fiber and water reducer. The carbon fiber accounts for 0.5% of the total mass of the neat paste, water and coarse and fine aggregates, the steel fiber accounts for 1.5% of the total mass of the neat paste, water and coarse and fine aggregates, the waste shell powder accounts for 1.5% of the total mass of the neat paste, water and coarse and fine aggregates, the rubber powder accounts for 1.5% of the total mass of the neat paste, water and coarse and fine aggregates, the glass fiber accounts for 1.0% of the total mass of the neat paste, water and coarse and fine aggregates, and the water reducer accounts for 0.5% of the total mass of the neat paste, water and coarse and fine aggregates.
[0119] The steel fiber is a wavy steel fiber with a diameter of 0.1 mm.
[0120] The carbon fiber is asphalt-based carbon fiber with a diameter of 5 μm.
[0121] The glass fiber is an alkali-resistant glass fiber with a diameter of 20 mm.
[0122] The water reducing agent is calcium lignin sulfonate.
[0123] Calcium hydroxide comprises the following preparation steps: N1. Limestone particles are sent from the raw material bin to the preheater to exchange heat with the high-temperature exhaust gas from the calcining furnace to increase the temperature of the limestone; N2, the preheated limestone enters the rotary kiln and decomposes into calcium oxide at 800℃; N3, calcium oxide reacts with water to obtain calcium hydroxide.
[0124] Water glass comprises the following preparation steps: P1, quartz sand and soda ash are mixed evenly in a weight ratio of 1:1.35, and the mixed raw materials are put into a high-temperature reverberatory furnace and calcined at a high temperature of 1400°C for one hour to generate molten sodium silicate; P2. Add sodium silicate granules into the steam ball and add water to form a water glass solution.
[0125] Sodium hydroxide comprises the following preparation steps: Q1. Dissolve the raw salt, remove impurities through filtration, sedimentation and ion exchange to obtain refined brine; Q2. Pass the refined brine into an electrolytic cell and pass direct current for electrolysis to obtain sodium hydroxide.
[0126] Example 5 The method for preparing cement concrete by adding a small amount of activated slag in a high alkaline environment comprises the following steps: S1. Use a crusher to crush large pieces of construction slag, and after drying, use a grading crusher to grind them into slag powder; S2, calcining the slag powder in step S1 to form activated slag, and mixing the activated slag with cement, a water reducing agent, and a retarder to form a mixture; S3, mixing sodium hydroxide, water glass and water to form an alkaline activator; S4, premixing the mixture of step S2 and the alkali liquor activator of step S3 for 15 minutes to form a geopolymer slurry, and adding the remaining admixtures, sand and gravel to stir to form concrete.
[0127] Furthermore, the construction slag in step S1 is crushed to a particle size of 3 mm, and the slag powder is ground into 0.75 mm; the crushed stone is made of granite crushed stone and slag crushed stone, and the granite crushed stone and slag crushed stone are mixed in a mass ratio of 1:1, and the crushed stone particle size is between 6 mm; the sand uses graded sand and gravel with a particle size of 1.5 mm.
[0128] The calcination method of activated slag comprises the following steps: M1. The ground slag powder is placed in a muffle furnace and heated from room temperature to 750°C at a rate of 15°C per minute, and maintained at 750°C for 2.5 hours; M2. After heating is completed, the temperature in the muffle furnace chamber is naturally cooled to room temperature to form calcined activated slag.
[0129] Calculated by mass, the ratio of 1.0% sodium hydroxide, water glass and water is 5:45:55.
[0130] The activated slag and cement are mixed in a mass ratio of 1:4 to form a mixture.
[0131] The weight ratio of the mixture, sand, crushed stone and alkali activator is 1.2:2.0:3.5:0.25. The admixture also includes carbon fiber, steel fiber, waste shell powder, rubber powder, glass fiber, retarder and water reducer. The carbon fiber accounts for 0.8% of the total mass of the pure paste, water and coarse and fine aggregates, the steel fiber accounts for 1% of the total mass of the pure paste, water and coarse and fine aggregates, the waste shell powder accounts for 0.5% of the total mass of the pure paste, water and coarse and fine aggregates, the rubber powder accounts for 1.5% of the total mass of the pure paste, water and coarse and fine aggregates, the glass fiber accounts for 1.0% of the total mass of the pure paste, water and coarse and fine aggregates, the retarder accounts for 0.1% of the total mass of the pure paste, water and coarse and fine aggregates, and the water reducer accounts for 0.3% of the total mass of the pure paste, water and coarse and fine aggregates. The steel fiber is a fine steel fiber with a diameter of 0.2 mm.
[0132] The carbon fiber is a carbon fiber with a diameter of 5 μm.
[0133] The glass fibers were chopped glass fibers with a diameter of 10 mm.
[0134] The retarder is sodium gluconate.
[0135] The water reducer is a polycarboxylic acid water reducer whose main chain is a copolymer of methacrylic acid and methyl acrylate and whose side chain is a polyoxyethylene.
[0136] Calcium hydroxide comprises the following preparation steps: N1. Limestone particles are sent from the raw material bin to the preheater to exchange heat with the high-temperature exhaust gas from the calcining furnace to increase the temperature of the limestone; N2, the preheated limestone enters the rotary kiln and decomposes into calcium oxide at 1200℃; N3, calcium oxide reacts with water to obtain calcium hydroxide.
[0137] Water glass comprises the following preparation steps: P1, quartz sand and soda ash are mixed evenly in a weight ratio of 1:1.35, and the mixed raw materials are put into a high-temperature reverberatory furnace and calcined at a high temperature of 1400°C for one hour to generate molten sodium silicate; P2. Add sodium silicate granules into the steam ball and add water to form a water glass solution.
[0138] Sodium hydroxide comprises the following preparation steps: Q1. Dissolve the raw salt, remove impurities through filtration, sedimentation and ion exchange to obtain refined brine; Q2. Pass the refined brine into an electrolytic cell and pass direct current for electrolysis to obtain sodium hydroxide.
[0139] Comparative Example 1 The main difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, the slag powder in step S1 is directly mixed with cement and part of the reinforcing agent to form a mixture. The remaining steps and component parameters of Comparative Example 1 are the same as those of Example 1.
[0140] Comparative Example 2 The main difference between Comparative Example 2 and Example 2 is that the mixed material of step S2 and the alkali liquor activator of step S3 are directly mixed with sand and gravel in Comparative Example 2. The remaining steps and component parameters of Comparative Example 2 are the same as those of Example 2.
[0141] Comparative Example 3 The main difference between Comparative Example 3 and Example 1 is that the reinforcing agent is omitted in Comparative Example 3, part of the admixture in step S2 is replaced by activated slag, and part of the admixture in step S4 is replaced by crushed stone. The remaining steps and component parameters of Comparative Example 3 are the same as those of Example 1.
[0142] Comparative Example 4 The main difference between Comparative Example 4 and Example 1 is that the steps of Comparative Example 4 are to stir activated slag, cement, alkali activator, admixture, sand and crushed stone to form concrete. The remaining steps and component parameters of Comparative Example 4 are the same as those of Example 1.
[0143] Comparative Example 5 The main difference between Comparative Example 5 and Example 1 is that in Comparative Example 5, part of the admixture in step S2 is adjusted to be fully added in step S4. The remaining steps and component parameters of Comparative Example 5 are the same as those of Example 1.
[0144] The testing standard is GB / T50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete" for RCM method to test the chloride ion permeability coefficient; GB / T50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete" for compressive strength and flexural strength testing. GB / T50080 is used for slump testing.
[0145] The test data are shown in Table 1 and Table 2: Table 1: Performance test results of Examples 1-5
[0146] Table 2: Performance test results of comparative examples 1-5
[0147] Specifically, as can be seen from Table 1, Examples 1-5 exhibit good mechanical properties, anti-penetration properties and processing properties. Examples 1-5 provide a method for preparing cement concrete with a small amount of activated slag in a high-alkali environment and a prefabricated formwork column. The engineering slag is crushed, dried, and ground, and then calcined and activated. Under the action of an alkaline activator, a green and low-carbon cementitious material is formed and added to cement concrete to reduce the amount of high-energy consumption and high-pollution cement. Example 1-5 The present invention uses concrete mixed with activated slag to make prefabricated formwork columns, which can give full play to its advantages of fast hardening, early strength, and high strength, and promote the development of building industrialization while reducing resource waste and environmental pollution.
[0148] It can be seen from Table 2 that the compressive strength and flexural strength of Comparative Example 1 are both worse than those of Example 1. Compared with Example 1, Comparative Example 1 directly mixes the slag powder in step S1 with cement and part of the reinforcing agent to form a mixture. The calcined slag can better react with the sodium silicate and other components in the water glass to form a gelled network with good adhesion and strength. Therefore, the mechanical properties and anti-permeability properties of Comparative Example 1 are worse than those of Example 1.
[0149] Comparative Example 2 Compared with Example 2, the mixture of step S2 and the alkali liquor activator of step S3 are directly stirred with sand and gravel. Water glass can further improve the cohesiveness of geopolymer slurry, and the combination of geopolymer slurry with sand and gravel can make the internal structure of concrete more compact. The mechanical properties, processing properties and anti-penetration properties of Comparative Example 2 are worse than those of Example 2.
[0150] Compared with Example 1, in Comparative Example 3, the reinforcing agent is omitted, part of the admixture in step S2 is replaced by activated slag, and part of the admixture in step S4 is replaced by crushed stone. Among the admixtures, carbon fiber, steel fiber, waste shell powder, rubber powder, glass fiber, and water reducing agent can improve the mechanical properties, structural tightness, and processing performance of concrete. Therefore, the detection performance of Comparative Example 3 is worse than that of Example 1.
[0151] Compared with Example 1, in Comparative Example 4, activated slag, cement, alkali activator, admixture, sand and gravel are stirred to form concrete. The mixing of all materials easily causes the alkali activator to react with other ingredients, resulting in the inability to smoothly form a cementitious network. Therefore, the detection performance of Comparative Example 4 is worse than that of Example 1.
[0152] Compared with Example 1, Comparative Example 5 adjusts part of the admixtures in step S2 to all of them in step S4. The calcined slag can react better with the sodium silicate and other components in the water glass to form a gel network with good adhesion and strength, and part of the admixtures can react in the geopolymer slurry in advance, thereby improving the structural compactness. Therefore, the detection performance of Comparative Example 5 is worse than that of Example 1.
[0153] Example 6 It also includes a prefabricated formwork column made of concrete obtained by mixing a small amount of activated slag into cement concrete under a high-alkali environment.
[0154] Specifically, the formwork column is made of alkali-activated concrete mixed with activated slag, and the commonly used cross-sectional size of the frame column is 600mmx600mm for analysis. The inner hollow diameter is 450mm, and the thinnest wall thickness is 75mm. Figure 1 and Figure 2 As shown. Alkali solution activated concrete has the characteristics of early strength. The prefabricated formwork columns can be demolded and transported in a short time. It has good fluidity and can be fully compacted when making formwork columns, which has better quality assurance.
[0155] The PM curve of the formwork column with 12 HRB400 steel bars of 25 mm diameter after pouring C40 concrete on site is as follows: Figure 3 As shown, the bearing capacity of ordinary Portland cement concrete columns can be fully achieved.
[0156] Compared with the prior art, the present invention has the following beneficial effects: effectively utilizing construction waste, reducing land waste and environmental pollution caused by landfill, turning construction waste into treasure, adding it to concrete to replace part of cement, reducing cement usage, and reducing environmental damage caused by cement production, which has good social benefits. Using activated slag to replace 25% of cement can achieve the same strength of cement concrete, and its production unit concrete has a total energy consumption of about 6%, a carbon dioxide production of about 10%, and a production cost of about 9% compared to 0% replacement of cement concrete. Using concrete mixed with activated slag to make prefabricated formwork columns can give full play to its advantages of fast hardening, early strength, and high strength, and promote the development of building industrialization while reducing resource waste and environmental pollution.
[0157] The above is a preferred embodiment of the present invention. Relevant personnel in this technical field may make several improvements and modifications without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing cement concrete by adding a small amount of activated slag in a high alkaline environment, characterized in that: The following steps are involved: S1. Use a crusher to crush large pieces of construction slag, and after drying, use a grading crusher to grind them into slag powder; S2, calcining the slag powder in step S1 to form activated slag, and mixing the activated slag with cement and part of the admixture to form a mixture; S3, mixing sodium hydroxide, water glass and water to form an alkaline activator; S4, premixing the mixture of step S2 and the alkali liquor activator of step S3 to form a geopolymer slurry, adding the remaining admixture, sand and gravel and stirring to form concrete.
2. The method for preparing cement concrete by adding a small amount of activated slag in a high alkaline environment according to claim 1, characterized in that: The construction slag in step S1 is crushed to a particle size of less than 5 mm, and the slag powder is ground to a particle size of less than 1.5 mm; the crushed stone is made of granite crushed stone and slag crushed stone, and the granite crushed stone and slag crushed stone are mixed in a mass ratio of 1:1, and the crushed stone particle size is between 4-7 mm; the sand is graded sand and gravel, and the particle size is less than 2.5 mm.
3. The method for preparing cement concrete by adding a small amount of activated slag in a high alkaline environment according to claim 1, characterized in that: The calcination method of activated slag comprises the following steps: M1. The ground slag powder is placed in a muffle furnace and heated from room temperature to 750°C at a rate of 15°C per minute, and maintained at 750°C for 2.5 hours; M2. After heating is completed, the temperature in the muffle furnace chamber is naturally cooled to room temperature to form calcined activated slag.
4. The method for preparing cement concrete by adding a small amount of activated slag in a high alkaline environment according to claim 1, characterized in that: Calculated by mass ratio, the ratio of 0.8-1.5% sodium hydroxide, water glass and water is 5-10:35-45:45-55.
5. The method for preparing cement concrete by adding a small amount of activated slag in a high alkaline environment according to claim 1, characterized in that: The activated slag and cement are mixed in a mass ratio of 1:4 to form a mixture.
6. The method for preparing cement concrete by adding a small amount of activated slag in a high alkaline environment according to claim 1, characterized in that: The weight ratio of the mixture, sand, crushed stone and alkali activator is 0.8-1.2:1.5-2.0:2.5-3.5:0.25-0.75, and the admixture includes at least three of carbon fiber, steel fiber, waste shell powder, rubber powder, glass fiber, retarder and water reducer.
7. The method for preparing cement concrete by adding a small amount of activated slag in a high alkaline environment according to claim 1, characterized in that: Calcium hydroxide comprises the following preparation steps: N1. Limestone particles are sent from the raw material bin to the preheater to exchange heat with the high-temperature exhaust gas from the calcining furnace to increase the temperature of the limestone; N2, the preheated limestone enters the rotary kiln and decomposes into calcium oxide at 800℃-1200℃; N3, calcium oxide reacts with water to obtain calcium hydroxide.
8. The method for preparing cement concrete by adding a small amount of activated slag in a high alkaline environment according to claim 1, characterized in that: Water glass comprises the following preparation steps: P1, quartz sand and soda ash are mixed evenly in a weight ratio of 1:1.35, and the mixed raw materials are put into a high-temperature reverberatory furnace and calcined at a high temperature of 1400°C-1500°C for one hour to generate molten sodium silicate; P2. Add sodium silicate granules into the steam ball and add water to form a water glass solution.
9. The method for preparing cement concrete by adding a small amount of activated slag to cement concrete under a high alkaline environment according to claim 1, characterized in that: Sodium hydroxide comprises the following preparation steps: Q1. Dissolve the raw salt, remove impurities through filtration, sedimentation and ion exchange to obtain refined brine; Q2. Pass the refined brine into an electrolytic cell and pass direct current for electrolysis to obtain sodium hydroxide.
10. Prefabricated formwork column, characterized in that: The concrete is made by using the method for preparing cement concrete by adding a small amount of activated slag in a high-alkali environment as described in any one of claims 1 to 9.